Fundamental relationships between 3D pore topology, electrolyte conduction and flow properties: Towards knowledge-based design of ceramic diaphragms for sensor applications. (5th June 2016) - Holzer, L.; Stenzel, O.; Pecho, O.; Ott, T.; Boiger, G.; Gorbar, M.; de Hazan, Y.; Penner, D.; Schneider, I.; Cervera, R.; Gasser, P.
Abstract: Porous Diaphragms in pH-Sensors must meet apparently contradicting requirements such has high conductivity vs. low permeability and low outflow rate of the electrolyte vs. high flow velocity. In this study we intend to lay the foundations for knowledge-based materials design, so that the required materials properties can be achieved. This approach is based on a quantitative understanding of the relationships between 3D topological parameters with the corresponding effective transport properties (flow/permeability and conductivity). All transport relevant topological parameters (i.e. tortuosity, constrictivity, porosity and hydraulic radius) are determined by FIB-tomography and 3D image analysis. Effective properties (conduction and flow) are determined a) by 3D numerical simulation and b) with experimental characterization. The experimental work includes fabrication and characterization of porous YSZ sintered at 1250, 1300 and 1350 °C. Fundamental relationships are established by comparison of topological data with results from simulation and from experiment. The following design guidelines are then postulated: a) flow properties are adjusted independently from the conduction via manipulation of the hydraulic radius, b) high local flow velocity and at the same time relatively low volume outflow can be achieved by adjusting the constrictivity via manipulation of sintering conditions and with addition of pore former. Graphical abstract: Highlights: Pore topology is characterized by FIB-tomography and 3D analysis. Effective properties (conduction, flow) are determined by simulation and experiment. Fundamental relationships between topology and effective properties are established. Design guidelines proposed for optimized pore structure and diaphragm properties.